Plasmodium falciparum TryThrA antigen synthetic peptides block in vitro merozoite invasion to erythrocytes (2006)
Tryptophan–threonine-rich antigen (TryThrA) is a Plasmodium falciparum homologue of Plasmodium yoelii-infected erythrocyte membrane pypAg-1 antigen. pypAg-1 binds to the surface of uninfected mouse erythrocytes and has been used successfully in vaccine studies. The two antigens are characterized by an unusual tryptophan-rich domain, suggesting similar biological properties. Using synthetic peptides spanning the TryThrA sequence and human erythrocyte we have done binding assays to identify possible TryThrA functional regions. We describe four peptides outside the tryptophan-rich domain having high activity binding to normal human erythrocytes. The peptides termed HABPs (high activity binding peptides) are 30884 (61LKEKKKKVLEFFENLVLNKKY80) located at the N-terminal and 30901 (401RKSLEQQFGDNMDKMNKLKKY420), 30902 (421KKILKFFPLFNYKSDLESIM440) and 30913 (641DLESTAEQKAEKKGGKAKAKY660) located at the C-terminal. Studies with polyclonal goat antiserum against synthetic peptides chosen to represent the whole length of the protein showed that TryThrA has fluorescence pattern similar to PypAg-1 of P. yoelii. All HABPs inhibited merozoite in vitro invasion, suggesting that TryThrA protein may be participating in merozoite–erythrocyte interaction during invasion.